2021
DOI: 10.1016/j.jebo.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Do gender wage differences within households influence women's empowerment and welfare? Evidence from Ghana

Abstract: This study has been prepared within the UNU-WIDER project Women's work-routes to economic and social empowerment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Women's empowerment is an attempt to promote women's sense of self-worth, their ability to make their own choices, and their right to influence social change for themselves and others (Annan et al, 2021;Danquah et al, 2021;Malekan, 2015;Meier zu Selhausen, 2016). It can be defined in several ways, including accepting women's viewpoints or seeking to seek them out, improving women's status through education, literacy awareness, and training.…”
Section: Introductionmentioning
confidence: 99%
“…Women's empowerment is an attempt to promote women's sense of self-worth, their ability to make their own choices, and their right to influence social change for themselves and others (Annan et al, 2021;Danquah et al, 2021;Malekan, 2015;Meier zu Selhausen, 2016). It can be defined in several ways, including accepting women's viewpoints or seeking to seek them out, improving women's status through education, literacy awareness, and training.…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors argue that the productivity gap would persist even if women shared the same characteristics as men, had equal access to resources for generating income, and were taken into account when making policy decisions [ 8 , 11 , 28 ]. The gender gap shrinking inside the family may provide women with more power, enhancing their access to productive inputs, increasing their responsibility for decision-making and bargaining power, and enhancing their ability to make their own decisions that are in their economic interest [ 3 , 29 ]. It has been shown that the gender difference in agricultural productivity is related to either the gender of the household head or the gender of the person who manages the farm at home, utilizing data and outcomes at the household level [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…(3) trade unions as a pressure group that influences parliament, government, and public administration as long as it concerns the interests of workers (Danquah et al, 2021). Throughout the 20th century, the trade union position has been generally accepted.…”
Section: Results and Discussion Legal Protection Of Employee Wage Rig...mentioning
confidence: 99%